Perceptions of learning success among younger generation Inuit in Ulukhaktok, NWT, Canada - Lalonde, G; Pearce, T (ArcticNet Inc., 2013)
This poster describes research that will examine perceptions of learning success among younger generation Inuit in a case study of Ulukhaktok, Northwest Territories, Canada. The objectives are: (1) characterize the education system in Ulukhaktok in terms of learning paradigm and goals; (2) document and describe the perceptions of younger generation Inuit on learning success; and (3) identify and describe opportunities to enhance education in Ulukhaktok and elsewhere in the Arctic. This will be accomplished by conducting surveys and semi-structured interviews with educators and Inuit students (grades 9-12) at Helen Kalvak Elihakvik (school) in Ulukhaktok. Th e research responds to a knowledge gap on the relevance and eff ectiveness of a western-based education system in the Arctic. Many agree that the formalization of education has displaced Inuit cultural identity and has contributed to the breakdown of traditional modes of learning, observation and apprenticeship. Education scores of young Inuit are among the lowest in the nation. Th is phenomenon may be caused by the constant infl ux of incoming new teachers or the fact that the curriculum and teaching styles are not adequately adapted to suit Inuit ways of learning. Meanwhile subsistence hunting and fi shing remain a valued part of Inuit culture, but there is concern that some younger generation Inuit may not be as well equipped to participate in subsistence, particularly under changing conditions with negative implications for food security, health and well-being, and economy. If education in the Arctic is to serve the interests of students and contribute to the development of healthy communities it must embody Inuit perceptions of learning success and values. Th is research aims to contribute to this renegotiation of education in the Arctic. Th e research is part of ArcticNet Project 1.1 Community Adaptation and IK-ADAPT (Inuit Traditional Knowledge for Adaptation to the Health Eff ects of Climate Change) supported by CIHR.